An Examination of Women Experiencing Obstetric Complications Requiring Emergency Care: Perceptions and Sociocultural Consequences of Caesarean Sections in Bangladesh (Journal of Health, Population and Nutrition, 2012)
Little is known about the physical and socioeconomic postpartum consequences of women who experience  obstetric complications and require emergency obstetric care (EmOC), particularly in resource-poor  countries such as Bangladesh where historically there has been a strong cultural preference for births at  home. Recent increases in the use of skilled birth attendants show socioeconomic disparities in access to  emergency obstetric services, highlighting the need to examine birthing preparation and perceptions of  EmOC, including caesarean sections. Twenty women who delivered at a hospital and were identified by  physicians as having severe obstetric complications during delivery or immediately thereafter were selected  to participate in this qualitative study. Purposive sampling was used for selecting the women. The study  was carried out in Matlab, Bangladesh, during March 2008August 2009. Data-collection methods included  in-depth interviews with women and, whenever possible, their family members. The results showed  that the women were poorly informed before delivery about pregnancy-related complications and medical  indications for emergency care. Barriers to care-seeking at emergency obstetric facilities and acceptance of  lifesaving care were related to apprehensions about the physical consequences and social stigma, resulting  from hospital procedures and financial concerns. The respondents held many misconceptions about  caesarean sections and distrust regarding the reason for recommending the procedure by the healthcare  providers. Women who had caesarean sections incurred high costs that led to economic burdens on family  members, and the blame was attributed to the woman. The postpartum health consequences reported by  the women were generally left untreated. The data underscore the importance of educating women and  their families about pregnancy-related complications and preparing families for the possibility of caesarean  section. At the same time, the health systems need to be strengthened to ensure that all women in clinical  need of lifesaving obstetric surgery access quality EmOC services rapidly and, once in a facility, can obtain  a caesarean section promptly, if needed. While greater access to surgical interventions may be lifesaving,  policy-makers need to institute mechanisms to discourage the over-medicalization of childbirth in a context  where the use of caesarean section is rapidly rising. DOI: http://dx.doi.org/10.3329/jhpn.v30i2.11309 J HEALTH POPUL NUTR 2012 Jun;30(2):159-171